Análises metabolômicas e influências de antifúngicos e da interação patógeno-hospedeiro na expressão gênica de adesinas e proteases em Candida albicans - Oliver, Josidel Conceição (2020)
Fungal infections are a public health problem especially in hospital settings where Candida spp. are the main causes of invasive fungal infections. Among the virulence factors of this fungus, we highlight the production of adhesins and aspartate proteases, which contribute to the adhesion and invasion of host tissues. Candida spp. exposed to phagocytes and/or subinhibitory antifungal concentrations may alter the expression of these proteins and increase the fungal virulence. This study aimed to evaluate virulence factors such as metabolomics, antifungal susceptibility and gene expression SAP2, SAP4, SAP9, SAP10, HWP1 and ALS3, from C. albicans clinical isolates interacting with macrophages after exposition by inhibitory and subinhibitory antifungal concentrations. Eight C. albicans strains were tested for susceptibility to the amphotericin B, caspofungin and fluconazole and all strains were susceptible, except the 221-V which was considered resistant to caspofungin. The identification of the isolates was confirmed by MALDI-TOF, and the metabolomic profile was analysed by 1H-NMR. 66 molecules were found in the metabolome, which are mainly involved in the tricarboxylic acid (TCA) cycle, in glycolysis and gluconeogenesis, in the metabolism of amino acids, lipids and nucleic acids. In addition, some molecules associated with fungal virulence have been found. The strain 221-V stood out showing high concentrations of trehalose, glucose, fumarate, arabitol and glycerol, which are associated with oxidative and osmotic stress response. Three strains were selected for phagocytosis and gene expression assays from the results of metabolomics and susceptibility. After Candida macrophage interaction assays, macrophages killed 34.18 ± 5.43%; 35.30 ± 7.12% and 34.81 ± 4.73% of yeast cells in strains 121, 221-V and SC5314, respectively. Regarding gene expression analysed by qPCR, the Candida-macrophage interaction upregulated the expression of the SAP2 (13.85 ± 1.95), ALS3 (5.81 ± 0.91) and HWP1 (15.66±3.29) genes when compared to the control. In general, treatment with subinhibitory concentrations of amphotericin B, fluconazole and caspofungin increased the expression levels of the analysed genes. The 221-V strain stood out because it increased the expression levels of the six genes evaluated after exposure to this antifungal SAP2 (75,85±10,69), SAP4 (32,19±15,93), SAP9 (6,91±0,85), SAP10 (55,38±25,19), ALS3 (11,81±4,60) and HWP1 (41,38±8,69) when it was compared to control. These results show that interaction with host cells and especially exposure to subinhibitory antifungal concentrations can increase C. albicans virulence. Subinhibitory concentrations may be used as empirical or prophylactic systemic treatment for patients with risk factors for invasive candidiasis, and may occur in therapeutic failure due to pharmacokinetic and/or pharmacodynamic parameters and dosing errors or time between the doses. In addition, understanding fungal pathogenesis may assist in the research and development of new therapeutics, such as candidiasis drugs, thus contributing to a reduction in the incidence of morbidity and mortality associated with fungal infections.